Ethics and academic integrity in doctoral training: the case of doctorates in education in Chilean universities - González-Acuña, Juan Carlos; Muñoz, Carla; Valenzuela, Jorge (Acta Bioethica, 2023)
This article analyzes to what extent and how training programs for future researchers in doctoral education address the challenge of integrating ethical training in their curricular design. Based on a documentary review of course plans and postgraduate programs in education active in Chile, the explicit presence of ethical aspects and academic integrity in their training plans was examined. Through a thematic analysis of the official documentation of the programs, we identified and analyzed various elements related to research ethics and academic integrity addressed in doctoral training, their prevalent approach normative or ethical discernment, their orientation proactive or preventive and the depth with which these aspects are treated. The results show that only one-third of the current programs explicitly address ethical training in research and that in these cases, their approach tends to emphasize more formal than substantive aspects, mainly limited to compliance with the informed consent protocol.